2013
DOI: 10.4314/jae.v15i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Maize Farmers’ Perception of Commercialization and Privatization of Agricultural Extension Services in North Senatorial District of Gombe State, Nigeria

Abstract: A survey of maize farmers in Gombe north senatorial district of Gombe state was conducted in 2010 on their perception on commercialization and privatization of agricultural extension services. A structured questionnaire was used to collect data from 100 maize farmers, which were randomly selected. Descriptive statistics and binary probit model were the tools of analyses. The results indicate that majority (83%) of the respondents were against commercialization and privatization of extension services. About 31%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…It is surprising that even farmers who had no access to extension services from private organizations are willing to pay only if these organizations decide to reach them. This finding is consistent with the finding of Shausi et al [13] who found that about 92% of farmers in Mpwapwa and Mvomero districts are willing to pay for agricultural extension services provided by various providers. This is because farmers see agricultural extension services are more potential in their agricultural activities.…”
Section: Resultssupporting
confidence: 92%
“…It is surprising that even farmers who had no access to extension services from private organizations are willing to pay only if these organizations decide to reach them. This finding is consistent with the finding of Shausi et al [13] who found that about 92% of farmers in Mpwapwa and Mvomero districts are willing to pay for agricultural extension services provided by various providers. This is because farmers see agricultural extension services are more potential in their agricultural activities.…”
Section: Resultssupporting
confidence: 92%
“…In Nigeria, it was found that the major constraints are weak institutional development, lack of cooperation by farmers, uncertainties experienced in agriculture and conflicts and corruption (Chukwuone et al, 2006). Another study in Nigeria found that the main barriers to the acceptance of commercialization/privatization of agricultural extension included high cost of inputs, low profit, poor quality of DAs, high farmer to DA ratio and financial constraints (Sa'adatu et al, 2011). The respondents were asked to prioritize some strategies to alleviate the challenges associated with this system.…”
Section: Constraints Facing Cost-sharing Extension Service Provision and Ways Outmentioning
confidence: 99%